2022
DOI: 10.1089/hum.2022.141
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Correction of Murine Mucopolysaccharidosis Type II by Engraftment of Ex Vivo Lentiviral Vector-Transduced Hematopoietic Stem and Progenitor Cells

Abstract: Mucopolysaccharidosis type II (MPS II, Hunter syndrome) is an X-linked recessive lysosomal disease caused by deficiency of iduronate-2-sulfatase (IDS). The absence of IDS results in the accumulation of the glycosaminoglycans (GAGs) heparan sulfate and dermatan sulfate. Currently, the only approved treatment option for MPS II is enzyme replacement therapy (ERT), Elaprase. However, ERT is demanding for the patient and does not ameliorate neurological manifestations of the disease. Using an IDS-deficient mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“… 28–31 This suggests that delivery of recombinant lysosomal enzymes to HV when administrated intravenously is inefficient. 32 In this study, we showed that HSPC-LVGT effectively treats Alcian Blue reactivity as well as lysosomal pathology of HV, as previously shown, 33 independently of the tag used. IDS immunoreactivity was detected as strong signal in the endothelial layer of the HV leaflet, while the rest of the valve tissue was devoid of IDS protein.…”
Section: Discussionsupporting
confidence: 80%
“… 28–31 This suggests that delivery of recombinant lysosomal enzymes to HV when administrated intravenously is inefficient. 32 In this study, we showed that HSPC-LVGT effectively treats Alcian Blue reactivity as well as lysosomal pathology of HV, as previously shown, 33 independently of the tag used. IDS immunoreactivity was detected as strong signal in the endothelial layer of the HV leaflet, while the rest of the valve tissue was devoid of IDS protein.…”
Section: Discussionsupporting
confidence: 80%
“…In most cases, codon-optimized human IDS was placed under the control of the MND (myeloproliferative sarcoma virus enhancer, negative control region deleted, dl587rev primer-binding site substituted)-derived MCU3 promoter, a strong ubiquitous promoter that resulted in an increase of IDS activity in bone marrow and plasma of 30- to 296-fold above activity in wild-type (WT) animals. 20 , 21 , 22 Nevertheless, the use of unmodified IDS in these studies caused only a partial reduction of GAG levels and pathology in the CNS. To improve the efficacy in brain, Gleitz and co-workers used human IDS-tagged C-terminally with ApoE2, an epitope tag derived from apolipoprotein E and able to undergo transcytosis across the BBB.…”
Section: Introductionmentioning
confidence: 84%
“…73 Various in vivo rAAV delivery strategies are under exploration for therapeutic protein delivery as well. [74][75][76] rAAV has been used to deliver transgenes for treatment of MPS I and MPS II into the central nervous system and currently there is an ongoing clinical trial using rAAV9 to deliver IDUA into the central nervous system of patients (NCT03580083). 39,77 However, metaanalysis of 255 rAAV clinical trials calls into question the cost, durability, immunogenicity, and toxicity of various in vivo rAAV gene therapies.…”
Section: Discussionmentioning
confidence: 99%